PENGARUH RASIO KECUKUPAN MODAL, RETURN ON ASSETS (ROA) DAN KREDIT BERMASALAH TERHADAP PENYALURAN KREDIT PADA BANK PERKREDITAN RAKYAT KOTA SURABAYA (2014-2018) - Mareta Ayu Mahardini (Program Studi Ekonomi Pembangunan, 2020)
The purpose of this study is to describe the development of credit and the financial performance of BPR in Surabaya, and analyze the effect of the Capital Adequacy Ratio (CAR), Return On Assets (ROA) and Non-Performing Loans (NPL) on lending to BPR in Surabaya. The population of this research is all BPR in the City of Surabaya and 7 BPR samples are taken. The data of this study were obtained from financial reports published by BPR Surabaya in 2014 - 2018. This study used panel data regression analysis. The results of the data analysis show that the Capital Adequacy Ratio (CAR), Return On Assets (ROA) and Non-Performing Loans (NPL) have a significant influence on lending.